Penerapan Bisnis Model Canvas pada Hasil Praktek Operasional Kuliner Indonesia sebagai Produk Usaha Komersial - Ita Fatkhur Romadhoni; Any Sutiadiningsih; Niken Purwidiani; Lilis Sulandari; Ila Huda Puspita Dewi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This research aims to analyze the business model canvas on traditional Indonesian pastry and beverage products, focusing on understanding the elements that make up an effective and sustainable business model. This research uses a qualitative approach by identifying nine key components in the Business Model Canvas, namely customer segmentation, value proposition, distribution channels, customer relationships, key resources, key activities, key partners, cost structure, and revenue streams. The main focus is on utilizing the uniqueness of traditional cake and beverage products that reflect the richness of Indonesian culture, as well as the challenges in maintaining competitiveness in the modern market. The results show that the value proposition of traditional Indonesian products, such as authentic flavors and natural ingredients, is the main attraction for consumers. However, distribution and marketing channels remain a challenge, given the lack of digital market penetration and understanding of technology-based marketing. In addition, the cost structure and revenue streams show potential for efficiency improvements through product innovation and strategic partnerships with small and medium-sized enterprises. This research provides important insights for culinary entrepreneurs to design more adaptive and sustainability-oriented business strategies in an increasingly competitive market.